2005
DOI: 10.1002/cne.20670
|View full text |Cite
|
Sign up to set email alerts
|

Effects of glossopharyngeal nerve section on the expression of neurotrophins and their receptors in lingual taste buds of adult mice

Abstract: The expression of neurotrophins and neurotrophin receptors is essential for the proper establishment and function of many sensory systems. To determine which neurotrophins and neurotrophin receptors are expressed in taste buds, and in taste buds of mice following denervation, antibodies directed against the neurotrophins and their receptors were applied to adult mouse gustatory tissue. Immunohistochemistry reveals that nerve growth factor (NGF)-like immunoreactive (LIR), tyrosine kinase (trk) A-LIR, trkB-LIR, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 78 publications
(76 reference statements)
2
39
1
Order By: Relevance
“…This type of nerve-independent mechanism functions to maintain adult Merkel cells (English et al, 1994;Kinkelin et al, 1999;SieberBlum et al, 2004). However, it is unlikely that neurotrophins act directly on taste buds via p75, since unlike previous reports (Fan et al, 2004;Yee et al, 2005), no p75-like immunoreactivity was observed in taste cells. Rather, it is possible that taste buds are lost in p75 À/À mice because p75 expressing gustatory neurons are lost.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…This type of nerve-independent mechanism functions to maintain adult Merkel cells (English et al, 1994;Kinkelin et al, 1999;SieberBlum et al, 2004). However, it is unlikely that neurotrophins act directly on taste buds via p75, since unlike previous reports (Fan et al, 2004;Yee et al, 2005), no p75-like immunoreactivity was observed in taste cells. Rather, it is possible that taste buds are lost in p75 À/À mice because p75 expressing gustatory neurons are lost.…”
Section: Discussioncontrasting
confidence: 84%
“…It has been reported that the p75 receptor is present not only in peripheral sensory neurons, but also in somatosensory receptor cells (i.e., Merkel cells) and taste cells (Fan et al, 2004;Yee et al, 2005). To verify these findings in the taste system, tongue sections were immunohistochemically labeled for the p75 receptor.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In rodents, bilateral resection of the glossopharyngeal nerves impairs taste bud growth [21,22], while re-establishment of innervation allows continuation of their development [21]. Additionally, innervation is required for the maintenance of taste buds: resection of the glossopharyngeal nerves in adult rodents leads to taste bud degeneration within a few weeks [21,22].…”
Section: Innervation and Taste Budsmentioning
confidence: 99%
“…Additionally, innervation is required for the maintenance of taste buds: resection of the glossopharyngeal nerves in adult rodents leads to taste bud degeneration within a few weeks [21,22]. This effect is reversible since the regeneration of nerve fibres permits the formation of functional new taste buds [21,22].…”
Section: Innervation and Taste Budsmentioning
confidence: 99%